New depository for paratypes of the species Metaphycus zdeneki Noyes & Lozada, 2005 (Hymenoptera: Encyrtidae) - Lozada, Pedro W. (2018)
Four paratypes, one male and three females, of the species Metaphycus zdeneki Noyes & Lozada, 2005, are deposited in the insect collection of Servicio Nacional de Sanidad Agraria (SENASA), Lima, Peru. The holotype and remaining paratypes are hold in the collection of the Natural History Museum (BMNH), London, England, and Museo de Historia Natural, UNMSM (MUSM), Lima, Peru.